Quality control mechanisms of protein biogenesis: proteostasis dies hard - Timothy Jan Bergmann; Giorgia Brambilla Pisoni; Maurizio Molinari (AIMS Biophysics, 2016)
The biosynthesis of proteins entails a complex series of chemical reactions that transform the information stored in the nucleic acid sequence into a polypeptide chain that needs to properly fold and reach its functional location in or outside the cell. It is of no surprise that errors might occur that alter the polypeptide sequence leading to a non-functional proteins or that impede delivery of proteins at the appropriate site of activity. In order to minimize such mistakes and guarantee the synthesis of the correct amount and quality of the proteome, cells have developed folding, quality control, degradation and transport mechanisms that ensure and tightly regulate protein biogenesis. Genetic mutations, harsh environmental conditions or attack by pathogens can subvert the cellular quality control machineries and perturb cellular proteostasis leading to pathological conditions. This review summarizes basic concepts of the flow of information from DNA to folded and active proteins and to the variable fidelity (from incredibly high to quite sloppy) characterizing these processes. We will give particular emphasis on events that maintain or recover the homeostasis of the endoplasmic reticulum (ER), a major site of proteins synthesis and folding in eukaryotic cells. Finally, we will report on how cells can adapt to stressful conditions, how perturbation of ER homeostasis may result in diseases and how these can be treated.